2004
DOI: 10.1055/s-2004-821243
|View full text |Cite
|
Sign up to set email alerts
|

Nemaline Rods and Complex I Deficiency in Three Infants with Hypotonia, Motor Delay and Failure to Thrive

Abstract: Three infants are described who had nemaline rods on muscle biopsy and isolated deficiency of complex I of the respiratory chain on biochemical analysis. They all manifested failure to thrive from birth, and hypotonia and muscle weakness within the first three months of life. Different genetic defects leading to isolated complex I deficiency have been described associated with a variety of morphological changes on muscle biopsy, but rods have not been described. Nemaline rods have been secondary phenomena in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Rods can be a secondary response to metabolic stress. Numerous rods were observed in a few patients with Complex I deficiency (Lamont et al 2004) and in both muscle and non-muscle cells in vitro, they can be induced by a variety of substances that cause energy shortage, including ATP depletion and heat shock proteins (Vandebrouck et al 2010). This in vitro study suggested that rods formed under different conditions vary with regard to their cofilin and α-actinin content.…”
Section: What Is a Nemaline Rod?mentioning
confidence: 99%
“…Rods can be a secondary response to metabolic stress. Numerous rods were observed in a few patients with Complex I deficiency (Lamont et al 2004) and in both muscle and non-muscle cells in vitro, they can be induced by a variety of substances that cause energy shortage, including ATP depletion and heat shock proteins (Vandebrouck et al 2010). This in vitro study suggested that rods formed under different conditions vary with regard to their cofilin and α-actinin content.…”
Section: What Is a Nemaline Rod?mentioning
confidence: 99%
“…Ragged red fibres are not usually observed in nuclear-encoded complex I defects but were reported in single cases with NDUFS4 , NDUFS7 , FOXRED1 and NUBPL mutations 32 52 72. In addition, occasional patients with nemaline rods and complex I deficiency have been reported,73 and in one of these cases mutations of the structural subunit NDUFB3 were identified recently 74…”
Section: Approaches To Diagnosismentioning
confidence: 99%
“… * The second mutation awaits identification, 1 published by Anderson et al (2004), ¤ Patient 6 was described by Lamont and co-workers in 2004 [6] …”
Section: Tablementioning
confidence: 99%